2004
DOI: 10.1111/j.1750-3639.2004.tb00048.x
|View full text |Cite
|
Sign up to set email alerts
|

CGH Pattern of Esthesioneuroblastoma and their Metastases

Abstract: Comparative genomic hybridization (CGH) was used to screen 22 esthesioneuroblastomas (ENB) from 12 patients including 12 primary tumors and 10 metastasis/recurrent lesions for chromosomal imbalances being the most extensive study so far. The analysis revealed a characteristic pattern consisting of deletions on chromosomes 3p and overrepresentations on 17q in up to 100% of cases. Other important alterations being detectable in more than 80% of cases were deletions on 1p, 3p/q, 9p, 10p/q along with overrepresent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 22 publications
3
34
0
3
Order By: Relevance
“…However, no statistically significant survival difference was found for these variables. Most ONBs do not exhibit balanced translocations and the presence of fusion genes in patient samples and cell lines [49, 50]. Early research improperly suggested ONB exhibiting a translocation (11;22)(q24;q12) and producing an EWS/FLI1 transcript, which might cause misclassification to primitive neuroectodermal tumors (PNETs) [51, 52].…”
Section: Cytogenetic Alterationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no statistically significant survival difference was found for these variables. Most ONBs do not exhibit balanced translocations and the presence of fusion genes in patient samples and cell lines [49, 50]. Early research improperly suggested ONB exhibiting a translocation (11;22)(q24;q12) and producing an EWS/FLI1 transcript, which might cause misclassification to primitive neuroectodermal tumors (PNETs) [51, 52].…”
Section: Cytogenetic Alterationsmentioning
confidence: 99%
“…Bockmuhl and co-workers applied conventional comparative genomic hybridization (CGH) to 12 primary and 10 recurrent or metastatic ONBs [50]. This group determined frequent cytogenetic alterations and those associated with worse prognosis and metastases (Table 1).…”
Section: Cytogenetic Alterationsmentioning
confidence: 99%
“…3 Moreover, the CGH studies of cytogenetic aberrations in olfactory neuroblastoma are few. [4][5][6] We performed an oligonucleotide-based aCGH analysis on 13 olfactory neuroblastoma samples, which, to the best of our knowledge, was the first time that array-based CGH was applied to study the copy number changes in this neoplasm. Several copy number changes reported in previous studies were observed in our study, with identical, overlapping, or slightly different minimal common regions of alteration.…”
Section: Discussionmentioning
confidence: 99%
“…Three olfactory neuroblastomas were studied by Riazimand et al 5 using conventional CGH, and amplification of whole chromosome 19, partial gains of 1p, 8q, 15q, and 22q, and deletions of 4q and 6p were detected. Szymas et al 6 studied a single olfactory neuroblastoma and found gains of whole chromosomes 4,8,11, and 14, partial gains of 1q and 17q, partial deletions of 5q and 17q, and whole chromosome losses of 16,18,19, and X. In our study, we applied for the first time an oligonucleotide-based array CGH (aCGH) to identify the most frequently occurring DNA copy number changes in 13 cases of olfactory neuroblastoma.…”
mentioning
confidence: 99%
See 1 more Smart Citation